Revisiting Value Configurations : A Multi-Dimensional Framework for Hybrid Forms and Transition Analysis - Johansson, Magnus (Journal of Innovation Management, 2025)
Stabell and Fjeldstad (1998) proposed three value configurations; the value shop, the value chain and the value network based on Thompson’s (1967) three technologies as a typology. However, that Thompson’s technologies constitute a typology has been criticized (cf Barbini and Neri, 2017). Also, research has highlighted increased shifts in value configurations and hybrid forms. Thus, the question arises: how can value configurations be classified and along what dimensions, in order to facilitate analysis of hybrid forms and changes between value configurations? This paper expands on the current literature on value configurations to provide a deeper understanding of how they can be classified, particularly in the context of contemporary organizations that utilize hybrid forms of value configurations and transition between them. A value configuration map is proposed where the value configurations are positioned along three key dimensions facilitating hybrid position and transition analysis.